2018
DOI: 10.3892/ol.2018.8795
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial one‑carbon metabolic pathway is associated with patient survival in pancreatic cancer

Abstract: The expression levels of one-carbon metabolic enzymes were investigated and observed to be correlated with clinicopathological parameters in patients with pancreatic cancer. Mitochondrial one-carbon metabolism comprises a network of biological reactions that integrate nutrient status with nucleotide synthesis, amino acid metabolism, antioxidant reduced nicotinamide adenine dinucleotide phosphate production and epigenetic methylation processes. Previous studies have reported that the hyper-activation of mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 11 publications
4
48
0
1
Order By: Relevance
“…81,82 Nevertheless, ALDH1L2 is highly expressed and presents as an independent prognostic factor for overall survival in melanoma, PDAC, and CRC. 77,78,83 Depletion of ALDH1L2 markedly decreases the NADPH/NADP + and GSH/GSSG ratios, reduces the circulating tumor cells in blood and alleviates the metastatic burden. 77,83,84 In addition, the expression of ALDH1L2 is upregulated by some certain drugs, such as thapsigargin and tunicamycin, endoplasmic reticulum stress inducers in immortalized human B cells, 85 mitotane, an adjuvant monotherapy used for treating adrenocortical carcinoma, 86 and the indomethacin, an anti-inflammatory agent in breast cancer cells.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 Nevertheless, ALDH1L2 is highly expressed and presents as an independent prognostic factor for overall survival in melanoma, PDAC, and CRC. 77,78,83 Depletion of ALDH1L2 markedly decreases the NADPH/NADP + and GSH/GSSG ratios, reduces the circulating tumor cells in blood and alleviates the metastatic burden. 77,83,84 In addition, the expression of ALDH1L2 is upregulated by some certain drugs, such as thapsigargin and tunicamycin, endoplasmic reticulum stress inducers in immortalized human B cells, 85 mitotane, an adjuvant monotherapy used for treating adrenocortical carcinoma, 86 and the indomethacin, an anti-inflammatory agent in breast cancer cells.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
“…77,78,83 Depletion of ALDH1L2 markedly decreases the NADPH/NADP + and GSH/GSSG ratios, reduces the circulating tumor cells in blood and alleviates the metastatic burden. 77,83,84 In addition, the expression of ALDH1L2 is upregulated by some certain drugs, such as thapsigargin and tunicamycin, endoplasmic reticulum stress inducers in immortalized human B cells, 85 mitotane, an adjuvant monotherapy used for treating adrenocortical carcinoma, 86 and the indomethacin, an anti-inflammatory agent in breast cancer cells. 87 Thus, further exploration of the association between the effects of these drugs on the ALDH1L2 expression and the cellular response to redox stress is needed.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
“…Other enzymes of the SGOCP play a key role in tumorigenesis. Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) is consistently up-regulated in many cancer types, and its expression significantly correlates with poor clinical outcome in breast cancer, pancreatic carcinomas, renal cell carcinoma, and leukemia and in a particularly aggressive metabolic subtype of hepatocellular carcinoma (HCC; Bidkhori et al, 2018;Lehtinen et al, 2013;Lin et al, 2018;Liu et al, 2014;Nilsson et al, 2014;Noguchi et al, 2018;Reina-Campos et al, 2019;Tedeschi et al, 2015). MTHFD2 is a dual-action enzyme (dehydrogenase and cyclohydrolase) that catalyzes the reversible conversion of 5,10methylene-THF into 10-formyl-THF in the mitochondria, while MTHFD1, its cytosolic counterpart, catalyzes an extra reaction (synthetase) to convert 10-formyl-THF into THF and formate ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Serine catabolism by SHMT2 has been shown to affect complex I protein expression by epigenetic regulation of DNA methylation [14] and mitochondrial tRNA [15,16]. These studies used inhibitors [13] or SHMT2 knock out methods [14,15,17] to impair SHMT2 function in cells. Our data showed that over-expression of SHMT2, a phenomenon seen in tumors, reduced ETC protein expression.…”
Section: Discussionmentioning
confidence: 99%